A specter haunting Europe : the myth of Judeo-Bolshevism - Hanebrink, Paul A. (Belknap Press of Harvard University Press, 2018)
In the 20th century, Europe was haunted by a specter of its own imagining: Judeo-Bolshevism. Fear of a Jewish Bolshevik plot to destroy the nations of Europe took hold during the Russian Revolution and spread across the continent. Paul Hanebrink shows that the myth of ethno-religious threat is still alive today, in Westerners' fear of Muslims....